(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the peculiarities of explanation and principles of division of words referred as colloquial or pedantic style in electronic dictionaries of Modern Ukrainian.